Political Developments in Zakho From February 8, 1963 To November 18, 1963 - Mohamed, Sherzad Z.; Monir, Rojin Ch. (Humanities Journal of University of Zakho, 2017)
This research entitled (Political Developments in Zakho from February 8, 1963 to November 18, 1963), studies an important stage in the history of Zakho area, and it talks about the most important developments that happened in Iraq and Kurdistan and their influence on Zakho city. The research consists of a preface (introduction) and two sections. In the preface part the political history of Zakho during the Royal reign (1921 – 1958) and the first Republican reign (1958 – 1963) has been addressed in brief. A brief clarification of the position (attitude) of Zakho concerning the most important events and political attitudes has been given. In the first section, the launch of the coup of February 8, 1963 and its impact on Kurdistan, in general, and on Zakho, in particular, has been tackled. It especially talks about the peace talks between the Iraqi government and the leadership of the Kurdish revolution which did not lead to a positive result. The second section studies the political and military developments in Zakho after the renewal of military operations on June 10, 1963, and the continuity of these operations until the president Abdul-Salam Arif Mohammed launched his coup on the Baathist allies on November 18, 1963. The conclusion includes the most important findings the study reached to